Comprehensive device modelling and performance analysis of MASnI3 based perovskite solar cells with diverse ETM, HTM and back metal contacts. (15th March 2021) - Deepthi Jayan, K.; Sebastian, Varkey
Highlights: Six ETMs, nine HTMs and ten back contacts were used for the modelling of solar cell. Non-toxic lead free perovskite absorber layer was used for modelling. A high theoretical PCE of 25.05% was achieved for the optimized device configuration. The absorber layer parameters and back metal contacts influenced device performance. Abstract: Perovskite materials can be considered as the backbone of photovoltaic industry owing to their remarkable electronic, optical, mechanical and electrical properties. In this work, the performance of lead-free methyl ammonium tin iodide (MASnI3 ) based perovskite solar cells with TiO2, PCBM, ZnO, C60, SnO2 and IGZO as Electron Transport Materials (ETMs), Cu2 O, CuSCN, CuSbS2, P3HT, PEDOT: PSS, NiO, CuO, CuI and SpiroMeOTAD as Hole Transport Materials (HTMs) and Au, W, Ni, Pd, Pt, Se, Ag, Cu, C and Fe as back contact metals is simulated using SCAPS 1D software package. The thickness, total defect density, shallow uniform acceptor density, valence band effective density and conduction band effective density of the absorber layer (MASnI3 ) are varied for each of the various possible layer configurations with the above mentioned ETMs, HTMs and back contact metals. After analysing various solar cell configurations, it is seen that Glass/FTO/PCBM/MASnI3 /CuI/Au exhibits optimum performance with a Power Conversion Efficiency (PCE) of 25.05%, Fill Factor (FF) of 69.23%, a short circuit current density (JSC ) of 34.26863 mA/cm 2 and an open circuit voltage (VOC ) of 1.0557 V. The solar cell configurations Glass/FTO/IGZO/MASnI3 /CuSbS2 /W and Glass/FTO/PCBM/MASnI3 /SpiroMeOTAD/Pd have a PCE of 24.94% each. The study on thermal stability shows that these device configurations are stable at 300 K.